Comparison of the engineering geological properties of near surface and deep sedimentary rocks of the Karoo Supergroup, South Africa - Van Rooy, J.L. (Jan Louis) (University of Pretoria, 2021)
Dissertation (MSc (Engineering Geology))--University of Pretoria, 2021.